The Effect of Employee Empowerment and Policy Implementation on The Quality of Public Services with Job Satisfaction as An Intervening Variable at The Indonesian Quarantine Agency - Sugiono, Edi; Alfaraby, Akhmad (International Journal of Management Science and Information Technology, 2025)
The success of an organization in achieving its objectives and addressing both external and internal challenges largely depends on the quality of its human resources (HR). Employee development through empowerment is key to improving organizational performance. HR empowerment involves granting authority, developing competencies, and assigning responsibilities, while also creating an organizational culture that fosters employee self-confidence. However, the implementation of empowerment policies often faces challenges, particularly in the context of complex bureaucratic structures. This study aims to analyze the relationship between HR empowerment, policy implementation, and the quality of public service at the Indonesian Quarantine Agency (Barantin). The research method used is a survey with an explanatory approach, and data analysis is conducted using SmartPLS software. The results show that employee empowerment does not significantly affect the quality of public service, likely due to suboptimal implementation and a rigid bureaucratic structure. In contrast, policy implementation has a positive impact on the quality of public service, as clear and effective policies can enhance service efficiency and accountability. Furthermore, employee empowerment has a positive effect on job satisfaction, which in turn contributes to improving the quality of public service. The study also finds that job satisfaction acts as a mediator between employee empowerment and the quality of public service, as well as between policy implementation and the quality of public service. Therefore, strategies to improve public service quality at Barantin need to integrate efforts to empower employees and implement effective policies, focusing on enhancing employee job satisfaction. Thus, this study contributes to the development of a more adaptive and responsive policy implementation model to meet community needs, thereby improving the overall quality of public service.